2020
DOI: 10.2298/jas2001061p
|View full text |Cite
|
Sign up to set email alerts
|

Quality parameters of sunflower oil and palm olein during multiple frying

Abstract: The refined sunflower and palm oils are used in the food industry for the production of fried potatoes. Literary data have shown that palm oil had less tendency to degradation than sunflower oil due to its fatty acid composition. However, palm olein is a palm oil fraction and therefore has a different composition of fatty acids. The aim of this study was to investigate the quality of the refined palm olein in relation to the refined linoleic type sunflower oil during the production of fried potatoes. The oil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…When the potato was continually fried 40 min a day, seven days a week at 165 °C, Paunović et al. (2020) discovered that the peroxide and acid values increased by 77.8% (2.25–4.00 mmol/kg) and 26.8% (0.56–0.71 mg KOH/g), respectively.…”
Section: Applications Of Palm Oil In the Food Industrymentioning
confidence: 99%
“…When the potato was continually fried 40 min a day, seven days a week at 165 °C, Paunović et al. (2020) discovered that the peroxide and acid values increased by 77.8% (2.25–4.00 mmol/kg) and 26.8% (0.56–0.71 mg KOH/g), respectively.…”
Section: Applications Of Palm Oil In the Food Industrymentioning
confidence: 99%
“…The dominant fatty acid in standard (linoleic type) sunflower oil is a linoleic, polyunsaturated, omega-6 fatty acid, followed by an oleic fatty acid, while the linolenic acid content is always less than 0.3%. The low content of linolenic acid is positive because this fatty acid contributes most to the oxidative instability of the oil (Paunovic ´et al 2020). Therefore, the main goal of this research was to investigate the effect of repeated process of frying upon two different oils-refined oleic/linoleic sunflower oil and to monitor the physicochemical and chromatic features of these oils after the process of frying degradation has occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the peroxide value and free fatty acid content of all oil samples taken after frying were significantly higher compared to initial values in palm olein before frying, as expected (Table 2). These parameters increased immediately in a very short period of frying time (Gunnepana and Nawaratne, 2015;Paunović et al, 2020). On the other hand, peroxide values and free fatty acid content in all oil samples taken after the frying process did not indicate a significant difference between samples (Table 2).…”
Section: Resultsmentioning
confidence: 88%
“…This can be explained by the fact that the frying period was too short (3 minutes) for numerous chemical reactions. However, during the prolonged frying process, as well as multiple frying, the peroxide value and fatty acid content could be significantly increased (Ebba et al, 2012;Gunnepana and Nawaratne, 2015;Paunović et al, 2020). As the frying time is prolonged, chemical reactions of hydrolysis, oxidation, isomerization and polymerization become more intense, and these oils have an unpleasant taste and aroma, and additionally become unsafe to the consumer health (Ebba et al, 2012;Kaleem et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation